Biometric recognition : 11th Chinese Conference, CCBR 2016, Chengdu, China, October 14-16, 2016, Proceedings /: 11th Chinese Conference, CCBR 2016, Chengdu, China, October 14-16, 2016, Proceedings. (2016) - Unknown
No abstract available